2020
DOI: 10.17263/jlls.803886
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of novice and experienced EFL teachers’ codeswitching in Chinese university EFL classroom

Abstract: Scholars have focused on codeswitching problems for more than 50 years and have different voices about using codeswitching in the EFL classroom. This study used mix method to explore the EFL teachers' and students' attitudes towards using codeswitching in their College English classroom and the differences between novice and experienced teachers when they were using codeswitching at their pedagogies activities. 24 EFL teachers and 243 undergraduate students were involved in quantitative research, and 4 EFL tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The findings suggest that the use of codeswitching is necessary when the situation requires the use of first language in the classroom to enable the learners to become more confident in mastering English. In the same vein, Wu et. al., (2020) likewise concluded that teachers and students have the same attitudes towards using codeswitching, and experienced teachers used this more frequently than novice teachers.…”
Section: Language Theorymentioning
confidence: 86%
“…The findings suggest that the use of codeswitching is necessary when the situation requires the use of first language in the classroom to enable the learners to become more confident in mastering English. In the same vein, Wu et. al., (2020) likewise concluded that teachers and students have the same attitudes towards using codeswitching, and experienced teachers used this more frequently than novice teachers.…”
Section: Language Theorymentioning
confidence: 86%
“…This finding indicates that the use of codeswitching is indispensable when the situation necessitates the use of L1 in the classroom to enable the learners to become more self-assured in mastering English (Biliková & Seresová, 2021). In the same vein, Wu et. al.…”
Section: How Prevalent Is Codeswitching On Subjects With English As A...mentioning
confidence: 86%
“…This study used a mixed-method approach that combined qualitative and quantitative methods (Khun-Inkeeree et al, 2021;Maharani & Subanji, 2018;Wu et al, 2020). By using a sequential explanatory design in this study, quantitative data becomes supporting data from qualitative data (Bátyi, 2017;Daguay-James & Bulusan, 2020).…”
Section: Methodsmentioning
confidence: 99%